Pengaruh Citra Destinasi terhadap Minat Berkunjung Kembali dengan Pengalaman Pengunjung sebagai Variabel Mediasi : Studi pada Wisata Kebun Raya Purwodadi Kabupaten Pasuruan - Ayu Siti Ni’mah Syuridiniah; Mulyono Mulyono; Wahju Wulandari (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to explore the influence of destination image on visitors' intention to revisit Purwodadi Botanical Gardens in Pasuruan Regency, and examine the role of visitor experience as a mediating variable. This study uses a quantitative approach with an explanatory method. Data were collected through an online questionnaire distributed to 100 respondents who were visitors to Purwodadi Botanical Gardens. Data analysis was conducted using the Partial Least Square - Structural Equation Modeling (PLS-SEM) technique with the assistance of SmartPLS software. The results showed that destination image did not have a significant direct influence on the intention to revisit. However, destination image was proven to have a significant influence on visitor experience. Furthermore, visitor experience had a significant positive influence on the intention to revisit. These findings indicate that visitor experience significantly mediates the relationship between destination image and revisit intention. These findings strengthen the relevance of the Stimulus-Organism-Response (SOR) Model and the Theory of Planned Behavior, which states that initial perceptions of a destination (stimulus) do not automatically influence behavior (response), but need to be internalized through meaningful experiences (organism). Therefore, managing positive and memorable experiences is key to building visitor loyalty. The practical implication of this research is the importance for managers of Purwodadi Botanical Gardens and other educational tourism destinations to prioritize developing the visitor experience. Strategies such as improving services, providing interactive educational facilities, and creating a comfortable and enjoyable atmosphere can contribute to creating memorable experiences that encourage visitors to return in the future.